Three-dimensional preservation of a non-biomineralized arthropod in concretions in Silurian volcaniclastic rocks from Herefordshire, England (Geological Society Publishing House, 2000)
Three-dimensional preservation of a non-biomineralized arthropod occurs in carbonate concretions in a volcaniclastic deposit from the Wenlock Series of Herefordshire, England. Specimens are preserved in calcite that co-precipitated with framboids and polyhedra of pyrite. The texture of the calcite indicates that it is a void infill. It forms a cast of the external surface of the arthropod, having precipitated after decay of even the most recalcitrant biological tissues. Incorporation of the fossils into concretions ensured their long term preservation but was not, at least in most examples, responsible for preventing potential collapse and occlusion of voids in the interval between the decay of tissues and the precipitation of calcite. The precipitation and/or accumulation of clay minerals adjacent to specimens during decay was important in this process, as were possibly the geotechnical properties of the ash itself. Limited dolomitization of the calcite around the edges of the fossils and in the matrix of the concretion occurred at a later stage.